Pemanfaatan Biofilter Alami untuk Perbaikan Kualitas Air Sumur di Desa Pemongkong, Kecamatan Jerowaru, Lombok Timur - Nur Alfatiha; Farra Nur Hidayatul Wachidah; Muhamad Danil Amin (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study aims to design and test the effectiveness of local-based natural biofilters in improving well water quality in Pemongkong Village, East Lombok. An experimental method using a Completely Randomized Design (CRD) was applied with three treatments of layered media (gravel, silica sand, zeolite, sponge, and cotton). The results indicated that the natural biofilter was effective in improving the physical and chemical parameters of the well water. The most significant reduction in Total Dissolved Solids (TDS) and salinity occurred in the treatment with a thicker zeolite layer. Dissolved Oxygen (DO) levels increased, although they did not yet meet the quality standards. Conversely, Biological Oxygen Demand (BOD) values increased due to an insufficient Hydraulic Retention Time (HRT). ANOVA analysis revealed that the variations in media composition had no statistically significant effect on all water quality parameters. Generally, this biofilter has the potential to reduce physical parameters, but further development regarding media design and aeration systems is required.